Spiritual Inspiration of Village Cadres and Inclusive Innovation of Bricolage in Rural Autonomy in China - Zhao, Qing; Yu, Mei; Liu, Liangcan; Li, Binghan; Feng, Li (Frontiers in Psychology, 2021)
In the context of rural revitalization, the innovative behavior of villagers is crucial to rural development. The current research cannot fully reveal the internal mechanism among the critical factors in this field. In the new area, the ties between village cadres and villagers were getting loose. Then, the interaction among village cadres' spiritual encouragement, villagers' nostalgia for hometown, innovation behaviors, and individual resilience will constitute the rural development model's internal driving force. Based on a survey of 274 villagers in 10 provinces and regions across the country, the study shows that village cadres' spiritual encouragement can promote villagers' innovative behavior. The villagers' emotional commitment to the villages play a mediating role in the effect of village cadres' spiritual encouragement on villagers' innovative behavior. This intermediary effect is positively moderated by villagers' resilience.